Identifikasi Miskonsepsi Mahasiswa Prodi Pendidikan Fisika Universitas Pasir Pengaraian Pada Materi Listrik Statis - Rindi Genesa Hatika; Ika Daruwati; Sohibun Sohibun (Jurnal Ilmiah Wahana Pendidikan, 2022)
Each student has different abilities in connecting physics concepts with natural phenomena. Students can also experience misconceptions when compiling the physics concepts they are studying, which can lead to differences between their own concepts and those formed by experts. Misconceptions can disrupt and hinder learning in subsequent concepts (Maison et al, 2020). Therefore, an analysis of misconceptions must be carried out at the beginning of learning, so that the teacher can plan the right learning process to overcome them. The research was carried out at the Physics Education Study Program FKIP Pasir Pengaraian University Semester 2 of the 2020/2021 Academic Year with 30 student participants. The test technique used is a four-level multiple choice diagnostic test. The results of a quantitative analysis of the data obtained from the diagnostic test using the four tier diagnostic test in Basic Physics II course found that 35% of students experienced misconceptions, 8% of students did not know the concept, 12% of students answered questions by guessing and 45% of students who understood or know the concept